Faktor-Faktor Penyertaan Masyarakat Dalam Medan Infodesa (MID): Kajian di Wilayah Kemajuan Terengganu Tengah - Nan Zakiah, Megat Ibrahim (2011)
The aim of this study was to identify whether there is a relationship between communication skills, personality and innovative characteristics with community participation in Medan Infodesa (MID). This study was conducted in MID which is located in the Lembaga Kemajuan Terengganu Tengah (KETENGAH) area. This study utilized quantitative method through the usage of a questionnaire. Three hundred and sixteen respondents were involved in this study. The questionnaire comprised of five parts; demographic details of respondents, communication skills, personality, innovation characteristics and community participation in MID. Questionnaire used in this study was adapted from previous studies. A Likert scale questionnaire which consists of four instruments namely the Communication Skills Instrument, Big Five Personality Scale, Innovation Characteristics of New Technologies and Participation Instrument in Information Communication Technology (ICT) Programme was used in this study. Statistics analysis of Pearson Product-Moment Correlation Coefficient (r), Analysis of Variance (One Way ANOVA), t-Test and Multiple Regression were used to analyze the data. The findings indicated that there was a significant relationship between communication skills with community participation in MID. The findings also showed that there was a significant relationship between personality with community participation in MID. Further, the findings also showed that there was a significant relationship between innovative characteristics with community participation in MID. Besides, it was found that there was no significant difference in community participation in relation to gender and age. However, there was a significant difference in the level of community participation in MID and the level of education. Multiple Regression analysis identified the main predictor for the level of community participation in MID was innovative characteristics. The implication of this study showed that KETENGAH need to create courses to improve communication skills and to develop better personality. At the same time, it should be made known to the society that innovative characteristics can contribute to community participation in the MID.